Pengaruh Pemberian Kompos dan Urea Pada Pertumbuhan Tanaman Mentimun (Cucumis sativus L.) - Hura, Drimus Operman; Zulfida, Ida; Miyarnis, Miyarnis (UNIVERSITAS LABUHANBATU, 2025)
This study aimed to evaluate the effect of compost and urea application on the growth of cucumber (Cucumis sativus L.). The experiment was conducted at the experimental field of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia (UPMI), using a Randomized Block Design (RBD) with four treatments of compost and urea combinations, namely K0U0 (0 kg compost + 0 g urea), K1U1 (1 kg compost + 10 g urea), K2U2 (2 kg compost + 20 g urea), and K3U3 (3 kg compost + 30 g urea), each replicated three times. The observed parameters were plant height and number of leaves at 2, 4, 6, and 8 weeks after planting (WAP). Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that compost and urea treatments, either applied individually or in combination, did not significantly affect plant height and leaf number of cucumber at all observation periods based on ANOVA and DMRT analysis. However, there was a tendency of increased average plant height and leaf number under the highest combined treatment (K3U3). This suggests that balanced fertilization with compost and urea has the potential to support cucumber vegetative growth, although under the present experimental conditions, the effect was not statistically significant. Keywords: compost, urea, growth, cucumber